Peran Kapasitas Tukar Kation Dalam Mempertahankan Kesuburan Tanah Pada Berbagai Jenis Tekstur Tanah - Harefa, Dian Faery Chrisnawaty; Zebua, Meiman (CV. SINAR HOWUHOWU, 2024)
This study aims to analyze the role of cation exchange capacity (CEC) in maintaining soil fertility with various types of textures. CEC is an important parameter that determines the ability of soil to absorb and exchange essential cations for plants, which is highly dependent on soil texture, organic matter content, and pH. The study was conducted using soil samples with sandy, sandy loam, loam, and clay textures. The results showed that clay-textured soil had the highest CEC, while sandy soil had the lowest CEC. Organic matter content was shown to increase CEC, especially in soils with coarse textures, while a more neutral or alkaline pH tended to increase CEC significantly. These findings provide a scientific basis for soil management practices that can improve fertility, such as organic matter addition and liming on acidic soils. This research contributes to the sustainable management of soil fertility, especially on farms with a wide variety of soil textures and chemical conditions